2013
DOI: 10.1016/j.neuron.2012.11.033
|View full text |Cite|
|
Sign up to set email alerts
|

RAB7L1 Interacts with LRRK2 to Modify Intraneuronal Protein Sorting and Parkinson’s Disease Risk

Abstract: SUMMARY Recent genome-wide association studies have linked common variants in the human genome to Parkinson’s disease (PD) risk. Here we show that the consequences of variants at 2 such loci, PARK16 and LRRK2, are highly interrelated, both in terms of their broad impacts on human brain transcriptomes of unaffected carriers, and in terms of their associations with PD risk. Deficiency of the PARK16 locus gene RAB7L1 in primary rodent neurons, or of a RAB7L1 orthologue in Drosophila dopamine neurons, recapitulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
496
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(537 citation statements)
references
References 48 publications
36
496
1
Order By: Relevance
“…130 and Beilina et al . 118 showed a genetic interaction between LRRK2 and Rab7L1; a genetic risk factor for sporadic PD.…”
Section: Lrrk2 Function In Vesicle Dynamics and Retromer Functionmentioning
confidence: 91%
See 1 more Smart Citation
“…130 and Beilina et al . 118 showed a genetic interaction between LRRK2 and Rab7L1; a genetic risk factor for sporadic PD.…”
Section: Lrrk2 Function In Vesicle Dynamics and Retromer Functionmentioning
confidence: 91%
“…118 showed a genetic interaction between LRRK2 and Rab7L1; a genetic risk factor for sporadic PD. Expression of G2019S ‐LRRK2 in primary neurons induced lysosomal swelling and accumulation of a component of the retromer complex; the mannose phosphate receptor 130. The mannose phosphate receptor is normally recycled between endolysosomes and the Golgi apparatus 131.…”
Section: Lrrk2 Function In Vesicle Dynamics and Retromer Functionmentioning
confidence: 99%
“…If viable, this therapeutic approach would not only turn out to be beneficial for AD, but perhaps also be useful for other disorders where endosomal dysfunction has been described, for example PD [23]. Several studies have recently implicated the retromer complex itself in PD [24][25][26]. To date, a dozen genes have been implicated in PD, including a point mutation (D620N) in Vps35, which results in autosomal dominant familial PD [27,28].…”
Section: Retromer In Other Diseasesmentioning
confidence: 99%
“…Immunofluorescence analyses on GFP-Rab29-expressing cells showed that Rab29 colocalizes with GM130 (cis-Golgi) and TGN46 (trans-Golgi network), similar to epithelial cells. 15,18,19 Rab29 also colocalized with Rab11, while a limited colocalization was observed with both Rab4 (recycling endosomes) and Rab5 (early endosomes) (Figures 1c-e). Based on our findings implicating IFT20 in TCR recycling 5,14 as well as on the association of TCRζ with Rab8 11 which is similar to IFT20 is implicated in ciliogenesis, 21 the colocalization of Rab29 with these proteins was assessed.…”
mentioning
confidence: 92%
“…15,16 Rab32 and Rab38 participate in the generation and traffic of melanosomes, 17 while Rab29 regulates retrograde endolysosome-to-Golgi trafficking of the mannose-6-phosphate receptor (MPR) in epithelial and neuronal cells. 18,19 Based on the implication of Rab29 in typhoid toxin trafficking to the plasma membrane from the SCV, 15 where Rab4 and Rab11 have also been observed, 20 here we assessed the role of Rab29 in the regulation of TCR recycling. The results identify Rab29 as a novel regulator of vesicular trafficking in T cells, acting as a complex with IFT20 and the Rabs Rab8 and Rab11 to control TCR recycling and IS assembly.…”
mentioning
confidence: 99%